2017
DOI: 10.1007/s12010-017-2502-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Antibody Assembly in E. coli Periplasm by Disulfide Bond Folding Factor Co-expression and Culture Optimization

Abstract: Molecular chaperones and protein folding factors of bacterial periplasmic space play important roles in assisting disulfide bond formation and proper protein folding. In this study, effects of disulfide bond protein (Dsb) families were investigated on assembly of 3F3 Fab, an antibody inhibitor targeting matrix metalloproteinase-14 (MMP-14). By optimizing DsbA/C co-expression, promoter for 3F3 Fab, host strains, and culture media and conditions, a high yield of 30 mg purified 3F3 Fab per liter culture was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…Largely, cysteine-rich proteins are formed as IBs in both the cytoplasmic and periplasmic compartments of E. coli [ 10 ]. Utilizing various strategies for molecular and protein engineering such as gene fusion technology, co-production of chaperones [ 11 ], use of engineered host E.coli strains [ 12 ], optimizing the growth conditions such as temperature, inducer concentration, and induction time, can often help in increasing the formation of efficient soluble protein production [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Largely, cysteine-rich proteins are formed as IBs in both the cytoplasmic and periplasmic compartments of E. coli [ 10 ]. Utilizing various strategies for molecular and protein engineering such as gene fusion technology, co-production of chaperones [ 11 ], use of engineered host E.coli strains [ 12 ], optimizing the growth conditions such as temperature, inducer concentration, and induction time, can often help in increasing the formation of efficient soluble protein production [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Studier’s autoinduction medium [ 84 ], the growth is supported at the beginning by glucose, and when glucose is exhausted protein expression is autoinduced by a diauxic shift to lactose utilization, while glycerol is also coutilized as a major carbon source during expression. The most recent EnBase ® medium (EnPresso, GmbH, Berlin, Germany), in which glucose, as a primary carbon source, is gradually provided from a soluble polysaccharide by biocatalytic degradation [ 85 ], has been successfully used for high-yield cytoplasmic and periplasmic expression of several proteins including antibody fragments [ 86 , 87 , 88 , 89 ]. Several studies have demonstrated that the yield of recombinant antibody fragments in E. coli significantly improves at growth temperature below 30 °C, likely due to the reduction of translation rate that favors proper Ig-like folding and reduces aggregation [ 90 , 91 , 92 ].…”
Section: E Coli As Microbial Expression Stem Fmentioning
confidence: 99%
“…Stress minimization results in the increased viability of cells and process robustness [ 70 , 94 ]. In the so-called Design of Experiments (DoE) setting [ 95 ] the optimization of the expression of recombinant Fab and scFv fragments in stress minimization conditions has been successfully achieved through the selection of media [ 70 , 88 , 96 , 97 ], screening of signal peptide sequences [ 67 , 68 , 75 , 98 ] and optimization of co-expressing chaperone proteins [ 56 , 88 , 99 , 100 , 101 , 102 ]. At the transcriptional level, the concept of “codon harmonization”, a sophisticated version of the codon usage optimization, has largely improved the expression of antibodies fragments [ 60 , 103 ].…”
Section: E Coli As Microbial Expression Stem Fmentioning
confidence: 99%
“…For proteins with more than one disulfide, interconversion is made possible by the disulfide isomerase DsbC, which is in turn regenerated by another protein, DsbD (12). Modulation of the Dsb system is commonly employed for the production of eukaryotic proteins possessing multiple disulfide bonds in E. coli such as antibodies (14). In these cases, fusions of the target construct to DsbA or co-expression of DsbA with glutathione supplementation are typically employed to increase the rate of disulfide bond formation in the periplasmic space (15).…”
Section: Statement Of Significancementioning
confidence: 99%